PRANATA HUKUM BERBASIS KEARIFAN LOKAL DALAM TATA KEHIDUPAN BERBANGSA DAN BERNEGARA - Asrori S, M. Hudi (Faculty of Law, Universitas Sebelas Maret, 2012)
AbstractIn the transition system of modern life with all the phenomena that arise, at present, there are patterns of local wisdom and the life that holds fast to the principle ofl ifeis based on national values and moral, as well as discipline and obedience to the rules applicable in the environment. It exists in the Java community, especially in the Palace of Yogyakarta Sultanate. The conceptof national and state basis for a civilizednation Indonesia based on the persistence of religion and practice their religion according to their beliefs. Constitutionally this concept set for thin the Grundnorm Pancasila and Undang Dasar1945. Institutions based on local wisdom (Java) as aservicein the life of the nation is to up hold the principle of national unity Bhineka Tunggal Ika, the work ethic Tan Hana Dharma Mangrowa, based on the principle, Manunggaling Kawulo Gusti, Golong Gilig implemented, with the credo of service Nyawiji, Greget, Sengguh and Ora Mingkuh, to realize Hamemayu Hayuning Bawono as a primary goal in the life of the nation is prosperous, fairly and prosperous